Cytokines 2020
DOI: 10.5772/intechopen.85476
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha: A Major Cytokine of Brain Neuroinflammation

Abstract: Tumor necrosis factor (TNF) is one of the most extensively studied cytokine with about 19 distinct superfamily members and many more to be found. Prominent among these members is tumor necrosis factor alpha (TNF-α) that is known to be a potent promoter of inflammation, as well as many normal physiological functions in homeostasis and health and antimicrobial immunity. Nuclear factor kappa-light-chain enhancer of activated B cells (NFκB) is one of the most important transcription factors that activate transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
(38 reference statements)
2
22
0
1
Order By: Relevance
“…It is important to highlight that the polymorphisms evaluated in this study affect the expression of their genes or function of the proteins, which act on the fetus’ brain, both in the context of development and inflammatory response [ 34 , 35 , 36 , 37 , 38 , 39 ]. Since the aim of this study was evaluating the role that these polymorphisms could have, in the context of the ZIKV infection, on the fetal brain development, we considered that it would be interesting to evaluate their frequency only in individuals with CZS and individuals who have been exposed in utero to the ZIKV infection but were born normal and, in this sense, the parents were not evaluated, since this analysis would not add information to answer to the aim of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that the polymorphisms evaluated in this study affect the expression of their genes or function of the proteins, which act on the fetus’ brain, both in the context of development and inflammatory response [ 34 , 35 , 36 , 37 , 38 , 39 ]. Since the aim of this study was evaluating the role that these polymorphisms could have, in the context of the ZIKV infection, on the fetal brain development, we considered that it would be interesting to evaluate their frequency only in individuals with CZS and individuals who have been exposed in utero to the ZIKV infection but were born normal and, in this sense, the parents were not evaluated, since this analysis would not add information to answer to the aim of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although these genes and polymorphisms have an important role in neurogenesis or neuroinflammation, they have not been described as capable of causing the phenotypes seen in CZS, such as microcephaly, among others outside the context of the ZIKV infection [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. This could mean that ZIKV infection potentiates the effect of these polymorphisms and, for this reason, they act on individuals’ susceptibility to CZS in the context of ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have used the pro-inflammatory cytokine TNF-α as a prominent biomarker to investigate proinflammatory responses (Muhammad, 2019). It is the case however that microglial responses to inflammation involve the complex release and functional interplay of many different cytokines (Lively and Schlichter, 2018).…”
Section: Gas6mentioning
confidence: 99%
“…This pathological condition is caused by the activation of the neuroimmune cells from the brain astrocytes and microglia. Deregulation of microglia and astrocytes, abnormal pro-inflammatory cytokines (CK) synthesis such as tumor necrosis factor-α (TNF-α), interleukin 1 beta (IL-1β), and interferon-γ (IFN-γ), and rise of reactive oxygen and nitrogen species are the most common aspects in neuroinflammation [1][2][3][4]. It has been demonstrated that neuroinflammation plays a pivotal role in many neurodegenerative diseases such as Alzheimer's and Parkinson's diseases, amyotrophic lateral sclerosis, Huntington disease, spinocerebellar ataxia, and multiple sclerosis [5,6].…”
Section: Introductionmentioning
confidence: 99%